Application of nursing terminology based on the Indonesian nursing standards (diagnosis, outcome, and intervention) on the quality of filling out documentation - Yuwanto, Mahmud Ady; Eliya Astutik, Emi; Eko Prasetyo, Rizki (University of Muhammadiyah Malang, 2023)
Introduction: So as to account for the implementation, Indonesian nurses must be able to provide comprehensive, independent in nursing care. Objectives: This study aims to determine how using standard nursing terminology affects the quality of nursing documentation. Methods: This study employs a quantitative approach and a quasi-experimental design with non-equivalent groups and no control group. All room nurses at the Kaliwates General Hospital in Jember participated in the research. Sampling strategy based on total sampling using the non-parametric Wilcoxon test, a questionnaire was analyzed as the instrument. Results: The p-value of the results was 0.000. After training and assistance with filling out nursing documentation, the quality score for filling out nursing documentation improves. High-quality nursing documentation promotes structured, consistent, and successful communication. Inadequate nurse-to-nurse communication causes care discontinuity and mistakes. Implementing standard Indonesian nursing terminology has several ramifications. Conclusions: Standard nursing language terminology has a significant impact on improving the quality of nursing documentation based on Indonesian Nursing Standards (diagnosis, outcome, and intervention). Hospitals are expected to establish nursing documentation standards and conduct regular monitoring.